2018
DOI: 10.23937/2469-5734/1510061
|View full text |Cite
|
Sign up to set email alerts
|

Acidity and Dental Erosion from Apple- and Grape-Juice (An in vitro and in vivo Report)

Abstract: Introduction: Dental erosion from acid drinks is known; in vitro with in vivo evidence that apple and grape juices cause erosion is rare. Aim: i) To test acidity (pH and buffering capacity) in vitro; ii) And assess if these juices leach calcium from teeth in vivo. Methodology: First: Six commercially available potable apple and grape juices were measured (six times each drink) for pH and buffering using 0.5 Molar NaOH with a Mettler DL 25 Automatic Titrator. The apple and grape juices were measured separately,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
(32 reference statements)
0
0
0
Order By: Relevance
“…The findings are consistent with previous studies that found high acidity of carbonated soft drinks and fruit juices and reported that prolonged exposure to these drinks leads to the dissolution and loss of dental hard tissues. 20,35,38 Additionally, a few studies have reported that most commercially available vitamin water products are acidic, 17,26,27 similar to our results, which identified the tested vitamin waters and herbal beverages as acidic.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings are consistent with previous studies that found high acidity of carbonated soft drinks and fruit juices and reported that prolonged exposure to these drinks leads to the dissolution and loss of dental hard tissues. 20,35,38 Additionally, a few studies have reported that most commercially available vitamin water products are acidic, 17,26,27 similar to our results, which identified the tested vitamin waters and herbal beverages as acidic.…”
Section: Discussionsupporting
confidence: 89%
“…30,31 Also, some of the fruits or herbs that were the main ingredients, such as tangerine, pineapple, tomato, apple, and roselle, are acidic in nature. [32][33][34][35][36] Finally, most vitamin waters contain vitamin C or ascorbic acid, which is acidic. 37 This study assessed dental erosion using the gravimetric method, which analyzed the weight loss percentage of dental hard tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In the research conducted by Villa et al [32], it can be seen that both pH and other qualitative factors depend on the type of raw material and its variety and therefore the results may differ significantly for one species. The pH of the strawberry, apple, and rose juices were similar to those reported by other authors [33][34][35][36].…”
Section: Sensory and Physicochemical Analysis Of Fruit Juice Formulat...supporting
confidence: 88%
“…Иногда употребление фруктовых соков, в частности, яблочного, может спровоцировать возникновение неспецифической диареи у младенцев. [25] При обнаружении подозрительных симптомов необходимо незамедлительно прекратить ввод нового продукта и обратиться за консультацией к педиатру.…”
Section: дневная норма яблочного сока для детей и взрослыхunclassified